Embedded software development for safety-critical systems - Hobbs, Chris (CRC Press, Taylor & Francis Group, 2016)
Embedded Software Development for Safety-Critical Systems discusses the development of safety-critical systems under the following standards: IEC 61508, ISO 26262, EN 50128, and IEC 62304. It details the advantages and disadvantages of many architectural and design practices recommended in the standards, ranging from replication and diversification through anomaly detection to the so-called "safety bag" systems